2009
DOI: 10.1073/pnas.0907002106
|View full text |Cite
|
Sign up to set email alerts
|

Restriction versus guidance in protein structure prediction

Abstract: Conformational restriction by fragment assembly and guidance in molecular dynamics are alternate conformational search strategies in protein structure prediction. We examine both approaches using a version of the associative memory Hamiltonian that incorporates the influence of water-mediated interactions (AMW). For short proteins (<70 residues), fragment assembly, while searching a restricted space, compares well to molecular dynamics and is often sufficient to fold such proteins to near-native conformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
2
37
0
Order By: Relevance
“…The process of folding a protein is inherently coupled to collapse. Monte Carlo search, which requires large fragments to remain rigid during moves, suffers from an inability of simple moves to rearrange in the collapsed state resulting in an inability to avoid steric clashes [47]. Then sampling even a well-funneled landscape in this way can be problematic for large structures if a simple move set is used.…”
Section: Searching and Sampling Methodsmentioning
confidence: 99%
“…The process of folding a protein is inherently coupled to collapse. Monte Carlo search, which requires large fragments to remain rigid during moves, suffers from an inability of simple moves to rearrange in the collapsed state resulting in an inability to avoid steric clashes [47]. Then sampling even a well-funneled landscape in this way can be problematic for large structures if a simple move set is used.…”
Section: Searching and Sampling Methodsmentioning
confidence: 99%
“…Although the C-terminus of IκBα extends to residue 317, previous experimental evidence had suggested that the sequence PESEDEE (residues 281–287) was necessary and sufficient for full NFκB-binding and DNA molecular stripping activity 1415, 18 . To more fully explore the role of the PEST sequence in molecular stripping, in this paper we present simulations in which the full distribution of conformers adopted by residues 281–292 in IκBα is explored using the multiple fragment memory approach which takes a somewhat agnostic view of the PEST structure treating it as if there were no direct crystal structure information available 1920 . In addition, we use the same protocol to analyze a charge-neutralized version of the PEST sequence.…”
Section: Introductionmentioning
confidence: 99%
“…While fully accurate protein structures can be used to predict folding kinetics quite well 29 , do lower resolution models like those obtained by homology modeling 30,31,32 or ab initio structure prediction 33,34,35 suffice for kinetic modeling? Here we show that if sufficient predictive accuracy is available short range attractive models can be used and direct transit to the folded state (like that usually found experimentally near T F ) will occur in the simulation and mechanisms near the folding midpoint properly delineated.…”
Section: Introductionmentioning
confidence: 99%